Surgical hip dislocation in fixation of acetabular fractures: Extended indications and outcome. Issue 2 (February 2022) - Abdelnasser, Mohammad Kamal; Refai, Omar; Farouk, Osama
Highlights: Surgical hip dislocation will offer 360 degrees visualization of the acetabulum as well as the femoral head. Managing acetabular fractures through this approach revealed acceptable functional outcomes. Concomitant injuries could be easily addressed through this approach, such as, roof impaction, intraarticular fragments and labral injuries. The technique is reproducible; however, the learning curve is steep and needs to be performed by experienced acetabular trauma surgeons. Abstract: Background: Surgical hip dislocation has been described as an excellent method for reduction and fixation of acetabular fractures. It allows a 360-degree access to the acetabulum and acetabular dome. However, reproducibility of this technique is still a concern. The primary outcome of this study was to investigate the short term functional and radiological outcome with the use of surgical hip dislocation in acetabular fractures. The secondary outcome was to describe different indications and methods of reduction using this technique. Methods: This is a retrospective consecutive case series for the use of surgical hip dislocation in acetabular fractures. Between July 2013 and February 2017, we used this technique to manage 36 cases of acetabular fractures. Two patients were lost to follow up leaving 34 patients eligible for the study. All surgeries were done by a 5-years and a 10-years' experience surgeons in pelvic and acetabular trauma surgeries. Through Gibson approach, we used the technique of surgical hip dislocation as described by the Bernese group. Different methods of fracture reduction were used. Intraoperative grading of cartilage injury was done using Disler's grading system. Postoperative fracture reduction was evaluated using the criteria described by Matta. Clinical evaluation was done using the modified Merle d'Aubigne ́ and Postel system. Results: The mean intra-operative blood loss was about 700 ± 35.4 ml. The mean units of blood transfused were 1 ± 0.1 unit. The mean surgical time was 135 ± 11.7 minutes. Anatomical reduction was achieved in 27 patients (79.4%). At a mean of 30 ± 16.8 months (median = 26 and IQR 22) follow up, the functional score was excellent in 5 (14.7 %), very good in 8 (23.5%), good in 9 (26.5%), fair in 2 (5.8%), and poor in 10 (29.4%) patients. Four patients (11.7%) developed AVN at a mean of 8 months postoperatively. Conversion to THA was done in 5 patients (14, 7%). Trochanteric osteotomy showed osseous healing in all cases. No patient developed nerve injury or infection. One patient developed severe (grade III) heterotopic ossification. Conclusions: Besides the indications of surgical hip dislocation mentioned before as reduction of the anterior column in T and Transverse fractures, associated femoral head fractures, intraarticular fragments, and labral injuries, it can be used in other indications as entrapped posterior wall, roof impaction, pure impaction injuries and cranial extension of the posterior wall fractures. The technique is reproducible; however, the learning curve is steep and needs to be performed by experienced acetabular trauma surgeons.